2012
DOI: 10.1089/scd.2011.0367
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Enhances the Self-Renewal and Therapeutic Potential of Mesenchymal Stem Cells from Human Adult Bone Marrow

Abstract: Insufficient cell number hampers therapies utilizing adult human mesenchymal stem cells (hMSCs) and current ex vivo expansion strategies lead to a loss of multipotentiality. Here we show that supplementation with an embryonic form of heparan sulfate (HS-2) can both increase the initial recovery of hMSCs from bone marrow aspirates and increase their ex vivo expansion by up to 13-fold. HS-2 acts to amplify a subpopulation of hMSCs harboring longer telomeres and increased expression of the MSC surface marker stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…19 The application of heparan sulfate, however, would overcome these drawbacks. 2,3 Here, we found that N,O-sulfated (mainly N,6-O sulfated) K5 polysaccharide can significantly enhance the efficiency of rat bone marrow stem cell chondrogenic differentiation. Specifically, this specific K5 polysaccharide modification promoted the synthesis of glycosaminoglycans and type II, alpha 1 collagen, likely through its binding to chondrogenic growth factor TGF-b1, a prerequisite to trigger the signaling cascade for chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…19 The application of heparan sulfate, however, would overcome these drawbacks. 2,3 Here, we found that N,O-sulfated (mainly N,6-O sulfated) K5 polysaccharide can significantly enhance the efficiency of rat bone marrow stem cell chondrogenic differentiation. Specifically, this specific K5 polysaccharide modification promoted the synthesis of glycosaminoglycans and type II, alpha 1 collagen, likely through its binding to chondrogenic growth factor TGF-b1, a prerequisite to trigger the signaling cascade for chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…2 Studies to improve the efficiency of these processes have revealed the significance of not only growth factors but also other bioactive macromolecules like polysaccharides to enhance the efficiency of stem cell expansion and differentiation. [3][4][5] Since polysaccharides are inherently stable and show good activity, they are very good agents for stem cell applications.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the study, control data generated in hMSCs grown in maintenance conditions [40] was compared to heparin-treated hMSCs in Figures 1A, 1B, 2 and 3. Experimentation with heparin was performed in parallel with studies using HS [40].…”
Section: Methodsmentioning
confidence: 99%
“…Experimentation with heparin was performed in parallel with studies using HS [40]. Data obtained with heparin and HS were analyzed separately to address distinct findings on different biological properties of hMSCs that emerged from the two datasets.…”
Section: Methodsmentioning
confidence: 99%
“…In order to reach sufficient amount of cells at early passages, new strategies have recently been applied. For instance, MSCs proliferation can be enhanced by adding extracellular matrix components to culture medium composition, without the need of using growth factors affecting MSC differentiation potential [89]. Estrada et al [90] showed that MSCs cultured at low oxygen tension (3 %) are more genetically stable and grow faster than in normoxic conditions (20 % oxygen).…”
Section: Strategies To Increase Mscs Migratory Survival and Prolifermentioning
confidence: 99%